2017
DOI: 10.1177/1474515117739619
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with implantable cardioverter–defibrillator: systematic review of randomized controlled trials

Abstract: There was no evidence of impaired QoL in patients with an ICD. However, ICD patients must be educated of all possible risks and benefits, including transitory declines in QoL after ICD shocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 35 publications
0
29
0
5
Order By: Relevance
“…Similarly, according to Engelmann and Pehrson there seems to be a possible enhancement of QoL in patients with atrial fibrillation after having undergone an invasive treatment, for example, ablation. 27 However, findings regarding QoL and implantation of a ICD are conflicting, 28 as some studies show an increase in QoL 9, 29 while others indicate a decrease in QoL post-implantation. 30,31 Tomzik et al concluded that it is unknown whether QoL relates to ICD therapy or not.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, according to Engelmann and Pehrson there seems to be a possible enhancement of QoL in patients with atrial fibrillation after having undergone an invasive treatment, for example, ablation. 27 However, findings regarding QoL and implantation of a ICD are conflicting, 28 as some studies show an increase in QoL 9, 29 while others indicate a decrease in QoL post-implantation. 30,31 Tomzik et al concluded that it is unknown whether QoL relates to ICD therapy or not.…”
Section: Discussionmentioning
confidence: 99%
“…Having a cardiac device is associated with more frequent out-patient visits, reinterventions and possibly anxiety, as the device is an always present reminder of the heart disease, but studies so far have yielded contradictory findings regarding quality of life [25,26]. Here we show that there is no difference between patients with or without cardiac devices in self-reported health-related quality of life.…”
Section: Quality Of Lifementioning
confidence: 51%
“…Quality of life studies were conducted in the primary prevention clinical trials. The body of data indicates there is no clear evidence of a reduction in quality of life associated with ICD placement . Nonetheless, a subset of patients who experience an ICD shock develop post‐traumatic stress disorder, which in turn is associated with significant adverse outcomes inclusive of premature death .…”
Section: Additional Considerationsmentioning
confidence: 99%